The Comprehensive Marginal Return Algorithm for the Dynamic S-WTA Problem with Time Windows - Wang, Jiagen; Bin, Xin; Ma, Weijie; Zhang, JingYu (Chinese Control Conference, 2025)
To better adapt to the actual situation, this study builds a mathematical model for the dynamic S-WTA problem with time windows. By constructing a missile damage probability model and radar detection probability model, the model is to minimize the expected remaining threat value of incoming targets, constrained by the number of sensor channels, target strike strategy, and weapon ammunition quantity. The solution quality depends on the relevance of the constructive rules to the problem; however, the rule of the classic marginal return algorithm is fixed. To overcome the problem of difficulty in enhancing the quality of a solution using the classic marginal return algorithm, a comprehensive marginal return algorithm is proposed based on the statistical marginal return algorithm. The experimental results indicate that the comprehensive marginal return algorithm can improve the final success rate compared to the classic marginal return algorithm.